Fiber Optofluidic Microlasers: Structures, Characteristics, and Applications. Issue 1 (10th December 2021) - Yang, Xi; Gong, Chaoyang; Zhang, Chenlin; Wang, Yanqiong; Yan, Guo‐Feng; Wei, Lei; Chen, Yu‐Cheng; Rao, Yun‐Jiang; Gong, Yuan
Abstract: Herein, recent progress in fiber optofluidic lasers and their applications in biochemical detection are reviewed. The unique properties of optical fibers are introduced for the development of optofluidic microlasers, including high quality factor, small mode volume, high aspect ratio, high reproducibility, and low cost. Optical fiber microresonators based on Fabry–Pérot cavity, microring resonator or photonic bandgap cavity are highlighted to provide optical feedback for optofluidic lasing. For applications, the capability of fiber optofluidic lasers is emphasized to perform biochemical analysis with ultrahigh sensitivity, fast response, high throughput, and disposable optical biodetection. The challenges and prospects for fiber optofluidic lasers are also discussed. Abstract : Fiber optofluidic laser (FOFL) is a new type of laser that employs an optical fiber as its laser resonator and microfluidic channel. Here the recent progress in fiber optofluidic lasers is reviewed, including the unique properties of optical fibers, the structures and fabrication of fiber microresonators, the characteristics and the applications of FOFL as microlasers and biosensors.